MODELS AND PROBLEMS OF USING DIGITAL PLATFORMS IN ONLINE TRADING (World Bulletin of Public Health, 2022)
In today's world, business conditions are changing rapidly. These changes affect all existing business models and the process of relationships between key market participants. The existing technological capabilities of interpersonal and business communications, the increasing requirements for the level of service and the speed of providing the required services dictate the need for fundamental changes in approaches to building a business. Therefore, more and more companies are coming to understand the need to introduce digital technologies and transform existing business models.